Impact of Workplace Conflict on Employees’ Performance in Commercial Banks of Nepal - Shrestha, Arbind; Singh, Balgopal (Journal of Economics and Management, 2023)
Employee performance among the employees has been found as a fundamental element influencing the workplace conflict of the organisation. The purpose of this study was to examine the Impact of Workplace Conflict on Employees’ Performance in Commercial Banks of Nepal. The variables included in the study were the relationship conflict, task conflict, and process conflict were independent variable and employee performance was dependent variable. A survey research design using questionnaire method on 5-point Likert scale was used to collect. The study was conducted with the sample size of 170 and the data were analysed through the use of descriptive statistics, correlation, regression, t-test and multi-collinearity test using SPSS software. The findings of the study have a R square value of 0.626 meaning that 62.6% of the variation in the dependent variable is explained by the independent variables while 37.4% is explained by other variables outside the model and also showed that there is a strong positive correlation between the dependent variable and the set of independent variables. The result showed that there is significant impact of RC, TC, PC on EP.